( - 3 ) ² = ( - 3 ) x (- 3 ) = 9
- 3 ² = - ( 3 ² ) = - 9
2007-09-17 20:14:33
·
answer #1
·
answered by Como 7
·
1⤊
0⤋
1. (-3)² = (-3)(-3) = 9
First: you have -3 in parenthesis; you have to multiply it by itself, twice. Two negatives equal a positive.
2. -3² = -3*3 = - 9
First: there is no parenthesis, you can also think of it as
-(3)^2 ... -(3*3)= -(9) = -9 in which, you distribute the negative sign with 9 in parenthesis.
P.S. The one gun kid & babydoll also have the right idea. they shown their work & it makes sense.
2007-09-13 21:10:54
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
2⤊
0⤋
My honors students have the hardest time understanding this.
(-3)^2 means -3 times itself -3 x -3 = 9
-3^2 means the opposite of 3 times itself -(3 x 3) = -9
unless the negative is in parentheses it is not being squared
2007-09-13 21:11:51
·
answer #3
·
answered by sfroggy5 6
·
1⤊
0⤋
(-3)^2 = (-3)(-3) = 9
-3^2 = -1 * 3^2 = -1 * 9 = -9
In the first case the negative is inside the ( ) so it is also squared. In the second case just the 3 is being squared.
2007-09-13 21:10:29
·
answer #4
·
answered by USMCBabydoll 2
·
2⤊
0⤋
the difference between (-3)^2 and -3^2 is in the former case it is whole square ,the square is on both - sign and 3 but in latter case the square is only on 3.
(-3)^2=(-3)*(-3)=9
-3^2=-(3*3)= -9
2007-09-21 09:09:30
·
answer #5
·
answered by syeda q 1
·
0⤊
0⤋
Do not worry that much both (-3)^2 and -3^2 are have
the same answer
actually,in solving equations
First do what is inside the ( )
second do solve power x^2+3
Third do multiply or divide *, /
Last do +, -
after you do these you will see the answer in front you....
GOOD LUCK
2007-09-21 12:52:20
·
answer #6
·
answered by Rayan Ghazi Ahmed 4
·
0⤊
0⤋
(-3)^2 = -3 * -3 = 9
-3^2 = - 3*3 = -9
2007-09-13 21:07:20
·
answer #7
·
answered by Anonymous
·
1⤊
1⤋
18
2007-09-13 21:09:41
·
answer #8
·
answered by Anonymous
·
0⤊
3⤋
(-3)^2 think of that as 1((-3)2^2)
and
-3^2 as -1(-3^2)
in both cases -3 squared=9
but 9*-1=-9
helpful I hope
2007-09-13 21:14:46
·
answer #9
·
answered by GOLD-FLAW 2
·
0⤊
0⤋
(-3)² = 9
-3² = -9
2007-09-13 21:07:23
·
answer #10
·
answered by questionMan 1
·
1⤊
2⤋